Visible and near-infrared upconversion photoluminescence in lanthanide-doped KLu3F10 nanoparticles. Issue 38 (14th October 2015) - Bian, Wenjuan; Wang, Ting; Guo, Yanmei; Yu, Xue; Xu, Xuhui; Qiu, Jianbei
<x xml:space="preserve">Abstract</x> Upconversion (UC) photoluminescent nanocrystals of Ln3+-doped KLu3F10 have been synthesized via a facile and environmentally-friendly hydrothermal route.